Proteomic analysis of mitochondria: biological and clinical progresses in cancer. (3rd October 2017) - Wang, Yang; Zhang, Jing; Li, Bin; He, Qing-Yu
ABSTRACT: Introduction : Mitochondria play important roles in regulating multiple biological processes and signalling pathways in eukaryotic cells, and mitochondrial dysfunction may result in a wide range of serious diseases, including cancer. With improvements in the identification of mitochondrial proteins, mitochondrial proteomics has made great achievements. In particular, this approach has been widely used to compare tumour cells at different stages of malignancy. Therefore, there is an urgent need to identify and characterize the function of mitochondrial proteins in cancer progression and to determine the involved mechanisms. Areas covered : We provide an overview of recent progress related to mitochondrial proteomics in cancer and the application of comparative mitochondrial proteomics in various biological processes, including apoptosis, necroptosis, autophagy and metastasis, as well as clinical progress in cancer. Proteomics-related reports were found using PubMed and Google Scholar databases. Expert commentary : Understanding both post-translational modification and post-translational processing is important in the comprehensive characterization of protein function. The application of comparative mitochondrial proteomics to investigate clinical samples and cancer cells will contribute to our understanding of the molecular interplay of mitochondrial proteins in the development of cancer. This approach will mine more biomarkers for diagnosis and prognosis and improve therapeutic outcomes among cancer patients.